Hybrid Simulation for Large-Scale AC/DC Power System by Serial Interaction Process - Zhang, Song; Li, Guoqing; Li, Shuguang; Liu, Xintong (Frontiers in Energy Research, 2021)
Electromechanical transient (EMT) and transient stability hybrid simulations can make full use of their fast solving ability and high-precision computing ability to accurately simulate the dynamic characteristics of large-scale AC/DC systems. This paper proposes to select the bus as the hybrid simulation interface bus in the AC system near the DC system, which can effectively improve the simulation accuracy of AC/DC system interaction. At the interface bus, Norton equivalent and Thevenin equivalent are applied to the EMT simulation side and electromechanical transient simulation side, respectively. The three-phase simulation data and three-sequence component simulation data are extracted respectively, and the serial iteration method is used for hybrid simulation calculation. Taking Zhangbei multi terminal AC/DC system as an example, this paper compares the hybrid simulation results with the EMT simulation results to verify the accuracy and effectiveness of the proposed hybrid simulation method.